Comparison of selection indexes for dairy goats in the tropics - doi: 10.4025/actascianimsci.v35i3.16049 - Lopes, Fernando Brito; Silva, Marcelo Corrêa da; Fioravanti, Maria Clorinda Soares; Facó, Olivardo; McManus, Concepta (Acta Scientiarum. Animal Sciences, 2013)
The selection process in dairy goat was evaluated by selection indexes. Basal population of 1,000 does, randomly mated by 50 unselected and unrelated bucks, was simulated. Eight selection indexes in two production systems (intensive - indexes I-IV and semi-intensive - indexes V-XIII) were compared. Three groups of dairy goats (A, B and C) were simulated with a respective intensity of 10, 25 and 50%. Each group was composed of five generations and each generation was replicated 20 times. All traits were simulated using matrices of direct additive genetic and the residual (co)variance and the effect of Mendelian segregation. Statistical analyses were performed by repeated measurements in time. Selection using the suggested indexes improved all traits. Selection indexes III and VII are suggested due to simultaneous production and reproduction trait improvement. Indexes IV and VIII are recommended when higher rates of total solids and somatic cell count occur and would correspond to differentiated payment for the milk.